2012 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--21700
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Studio Pedagogy, Part 2: Self-regulated Learning and Blended Technology Instruction

Abstract: is a professor in the Department of Electrical, Computer, and Systems Engineering where he teaches courses on plasma physics, electromagnetics, electronics and instrumentation, electric power, and general engineering. His research involves plasma physics, electromagnetics, photonics, engineering education, diversity in the engineering workforce, and technology enhanced learning. Since joining the Rensselaer faculty in 1974, he has been continuously involved in research programs at such places as Oak

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Essentially all of these papers report learning gains through the use of these powerful and generally inexpensive platforms. A sampling of the best of these papers is found in the references [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]21]. One of the most elegant studies has been reported in a series of papers by Ferri et al [7] from Georgia Tech where they added hands-on modules using myDAQs in a variety of courses that previously had no experimental component.…”
Section: Introductionmentioning
confidence: 99%
“…Essentially all of these papers report learning gains through the use of these powerful and generally inexpensive platforms. A sampling of the best of these papers is found in the references [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]21]. One of the most elegant studies has been reported in a series of papers by Ferri et al [7] from Georgia Tech where they added hands-on modules using myDAQs in a variety of courses that previously had no experimental component.…”
Section: Introductionmentioning
confidence: 99%